2024
DOI: 10.1186/s12916-024-03274-6
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the potential association between GLP-1 receptor agonists and suicidal or self-injurious behaviors: a pharmacovigilance study based on the FDA Adverse Event Reporting System database

Jianxing Zhou,
You Zheng,
Baohua Xu
et al.

Abstract: Background Establishing whether there is a potential relationship between glucagon-like peptide 1 receptor agonists (GLP-1RAs) and suicidal or self-injurious behaviors (SSIBs) is crucial for public safety. This study investigated the potential association between GLP-1RAs and SSIBs by exploring the FDA Adverse Event Reporting System (FAERS) database. Methods A disproportionality analysis was conducted using post-marketing data from the FAERS reposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…GI adverse effects, including oily fecal spotting (27%), fecal urgency (22%), and steatorrhea (20%), are common in the first year of orlistat use, but typically resolve within 4 weeks and can be reduced by adhering to a low-calorie diet with less than 30% of calories from fat (Table 3). Because of its mechanism of action, orlistat should be administered with meals containing some fat (10%-30% of calories) to be effective and limit adverse effects.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…GI adverse effects, including oily fecal spotting (27%), fecal urgency (22%), and steatorrhea (20%), are common in the first year of orlistat use, but typically resolve within 4 weeks and can be reduced by adhering to a low-calorie diet with less than 30% of calories from fat (Table 3). Because of its mechanism of action, orlistat should be administered with meals containing some fat (10%-30% of calories) to be effective and limit adverse effects.…”
Section: Methodsmentioning
confidence: 99%
“…Clinicians should review all information available in the package insert for each medication prior to prescribing to be aware of all contraindications. In general, antiobesity medications are contraindicated among pregnant persons and individuals with known hypersensitivity to medication ingredients and are used cautiously in patients who are lactating. c Medication is approved by the US Food and Drug Administration as Schedule IV controlled substance; therefore, prescribers need to adhere to federal and state regulations for prescribing and dispensing these types of medications. d As of March 2024, package inserts for liraglutide, semaglutide, and tirzepatide include a warning about the risk of SI; however, no increased risk of suicide has been identified in monitoring studies, which was acknowledged by the US Food and Drug Administration in January 2024.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some concerns have been raised among healthcare professionals over the safety profiles of GLP-1 Ras. There have been reports of suicidal or self-injurious behaviors (SSIBs) to the European Medicines Agency (EMA), although pharmacovigilance reviews have reported no direct link between GLP-1 RAs and SSIBs ( Chen et al, 2023 ; Chen et al, 2024 ; Zhou et al, 2024 ). Increased risks of thyroid cancer and cholecystitis have been reported ( He et al, 2022 ; Bezin et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%